Paradigma Ekonomi Biru untuk Pembangunan Pesisir Indonesia - Wawan Sugianto; Yan Hermansyah; Sartika Sartika (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Indonesia, as the world’s largest archipelagic state, possesses significant potential in marine and fisheries resources, both in terms of natural assets and ecosystem services; however, its utilization remains suboptimal, with relatively low contributions to national GDP and persistent challenges such as ecosystem degradation, spatial-use conflicts, and coastal community poverty. This study employs a qualitative-descriptive approach through literature review and policy analysis based on secondary data from official government documents, national regulations, and relevant academic sources. The findings indicate that the blue economy paradigm and the Integrated Coastal Zone Management (ICZM) approach provide the most relevant conceptual frameworks to address Indonesia’s coastal development challenges. The blue economy emphasizes sustainable utilization of marine resources with a focus on community welfare, while ICZM offers mechanisms for cross-sectoral integration grounded in ecosystem-based management. By combining these approaches, Indonesia’s coastal and marine development can be directed toward balancing economic, social, and environmental interests, thereby supporting the nation’s vision as a global maritime axis.